Effects of Ingredient Substitution on Processed Cheese - Ahmad, Karimah (1996)
The availability of a wide range of quality palm products ranging from crude to fully refined, its flexibility and reliability o f supply had enabled the substitution of palm blend for milkfat. Furthermore, milk fat contains saturated fatty a high cholesterol content is considered to be a health liability. The fatty acid composition(FAC)of commercial processed cheese and matured cheddar cheese,confirmed that milkfat was the sole fat source in both samples. Commercial processed cheese was used as an external control and matured cheddar cheese as an ingredient in the processed cheese formulation. The solid fat content(SFC),FACand slip melting point (SMP)of different palm fractions were studied. The blending of different palm fractions were conducted and one with the closest SFC profile compared to milkfat was selected to partially replace milkfat in the experimental processed cheese formulation.Palm blend comprising 30% palmoil and 70% palm kernel olein was found to be most compatible to milkfat. The SFC of the blend was furt her improved by random interesterification(IE).